Preparation and characterization of hyperbranched poly(ether sulfone) and its application as a coating additive for linear poly(ether sulfone). Issue 36 (1st June 2016) - Han, Bing; Sun, Dong; Li, Xiujie; Gao, Cong; Zhang, Shuling
ABSTRACT: Hyperbranched poly(ether sulfone) (HPES), a suitable coating additive for improving the rheological properties of linear poly(ether sulfone) (LPES), was easily produced via polymerization of commercially available bisphenol S (A2 monomer, BPS) and synthesized 2, 4′, 6‐trifluoro‐phenylsulfone (BB′2 monomer, TF). During this reaction, fluoro‐ or phenolic‐terminated HPES (F‐HPES or OH‐HPES) could be facilely obtained by controlling the feed mole ratios of the two monomers. The polymerization mode A2 + BB′2 was confirmed by analyzing the model compounds and the degree of branching (DB) was calculated systematically. In addition, the synthesized polymers' chemical structures were exhibited by FTIR, 1 H NMR as well as 19 F NMR spectroscopy. Notably, the addition of 1 wt % HPES reduced the melt viscosity and improved the high temperature liquidity of LPES because of its unique spherical shape. Furthermore, the addition of HPES did not have a negative impact on the performance of LPES, which was attributed to the good miscibility between HPES and LPES. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 43892. Abstract :